PENDEKATAN KUALITATIF TENTANG PERSPEKTIF GENERASI PENERUS TENTANG PENGELOLAAN BISNIS KELUARGA YANG IDEAL - Anita Maharani; Suroyo Gino; Zainur Hidayah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to learn about the perspectives of the second generation of family company owners on governance, work performance, and ideal leadership for the family business to succeed. The evolution of family business studies that look at governance, work performance, governance, and leadership is discussed in some of the literature examined in this study. The Hasnur Group is the subject of this study, and the data is processed by showing data reduction before being evaluated using descriptive techniques. The findings of this study show that the second generation has a unique viewpoint on governance, namely that it should be handled by the family, that work performance should be guided by the principles established by the second generation, and that leadership should use situational leadership